EFEKTIFITAS LIFE REVIEW THERAPY TERHADAP PENURUNAN DEPRESI PADA LANSIA DI POSYANDU GATOT KOCO DESA PAKISAJI KAB. MALANG - Khoirul Nikmah; Sih Ageng Lumadi; Lilla Maria (Jurnal Kesehatan Mesencephalon, 2020)
The negative impact of decreased bodily functions and psychosocial changes in the elderly can cause depression. One of the therapies that can reduce depression in the elderly is Life Review Therapy. The purpose of this study was to decide the effectiveness of Life Review Therapy on reducing depression in the elderly. This type of pre-experimental research with one group pre-post test design method. Population 47 elderly. The technique of sample retrieval used total sampling. A sample of 47 elderly. Instrument using GDS. Analyze data with the Wilcoxon test. The result of this research showed that level of depression in the elderly before given Life Review Therapy experienced mild depression 47 respondents 100%, the level of depression in the elderly after being given Life Review Therapy became normal 30 respondents 63.8% and mild depression 17 respondents 36.2%, there was a significant effect on Life Review Therapy for decreasing the level of depression in the elderly, with a p value of 0,000. The result of the study concluded that Life Review Therapy was effective in reducing depression in the elderly. Further research suggestions are given more attention to the number and availability of photos for each theme so that there can be time uniformity during therapy, and the questions are more varied.Keywords: Life Review Therapy, Depression, Elderly